Significance of Financial Stability in Commercial Banks - Azimova Khulkar Egamberdiyevna (European Science Publishing, 2023)
This article describes the issues of financial stability of commercial banks and analyzes them on the basis of statistical data. The Strategy for Banking Reform in the Republic of Uzbekistan for 2020-2025 covers the main tasks of commercial banks, their role in the implementation of modern and quality banking services on the basis of tables and statistical analysis. It also provides conclusions and recommendations for further improving the financial stability of commercial banks.
Keywords: loan portfolio, liquidity, total capital, bank balance, deposit, bank asset, credit investments.